GENERALIZED ORDER \((α ,β)\) ORIENTED SOME GROWTH PROPERTIES OF COMPOSITE ENTIRE FUNCTIONS - Tanmay Biswas; Chinmay Biswas (Ural Mathematical Journal, 2020)
In this paper we establish some results relating to the growths of composition of two entire functions with their corresponding left and right factors on the basis of their generalized order \((α ,β )\) and generalized lower order \((α ,β )\) where \(α \) and \(β \) are continuous non-negative functions on \((-∞ ,+∞ )\).